2014
DOI: 10.1007/s00421-014-3002-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on body temperature in otherwise-healthy females when controlling hydration and heat production during exercise in the heat

Abstract: When obese and non-obese females exercised at a fixed metabolic heat production and euhydration was maintained, there were no differences in body temperature between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
22
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
2
22
1
4
Order By: Relevance
“…Nonetheless, Adams et al (2014) reported similar changes in core temperature between groups in both trials, potentially indicating that either, (1) heat dissipation may have actually have been inhibited in the obese group; or (2) a lower heat storage was required for a given change in their core temperature secondary to a lower specific heat capacity in the obese group.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Nonetheless, Adams et al (2014) reported similar changes in core temperature between groups in both trials, potentially indicating that either, (1) heat dissipation may have actually have been inhibited in the obese group; or (2) a lower heat storage was required for a given change in their core temperature secondary to a lower specific heat capacity in the obese group.…”
mentioning
confidence: 64%
“…the amount of secreted sweat that evaporates from the skin) is not different. In light of this, we offer an alternative interpretation of the data presented by Adams et al (2014).…”
mentioning
confidence: 83%
See 3 more Smart Citations